2011
DOI: 10.1021/ja202375y
|View full text |Cite
|
Sign up to set email alerts
|

Low-Valent Ene–Amido Iron Complexes for the Asymmetric Transfer Hydrogenation of Acetophenone without Base

Abstract: Examination of the role of base in the activation of our previously reported iron(II) complexes having the general formula [Fe(CO)(Br)(PNNP)][BPh(4)] revealed a five-coordinate iron(II) complex in which the tetradentate PNNP ligand had been doubly deprotonated. The new iron(II) complexes were used in the transfer hydrogenation of acetophenone in isopropanol in the absence of added base, and certain analogues showed catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 36 publications
1
93
0
Order By: Relevance
“…If the ethyl group on phosphorus of 46 was replaced by bulky Cy or iPr substituents, the corresponding complexes were inactive for TH, which was attributed to the inactivity of their parent compounds. 279 The same research group also reported that when activation of the 282 This result suggested that partial ligand reduction is the key for high catalytic activity and that an outer-sphere mechanism is more probable for iron−PNNP promoted TH.…”
Section: Scope Of the Reviewmentioning
confidence: 93%
“…If the ethyl group on phosphorus of 46 was replaced by bulky Cy or iPr substituents, the corresponding complexes were inactive for TH, which was attributed to the inactivity of their parent compounds. 279 The same research group also reported that when activation of the 282 This result suggested that partial ligand reduction is the key for high catalytic activity and that an outer-sphere mechanism is more probable for iron−PNNP promoted TH.…”
Section: Scope Of the Reviewmentioning
confidence: 93%
“…[23] However, this catalyst is generated by first reacting a precursor with a strong base, isolating it and finally applying it in catalysis. [23] However, this catalyst is generated by first reacting a precursor with a strong base, isolating it and finally applying it in catalysis.…”
Section: Mechanistic Investigations Of the Transfer Hydrogenation In mentioning
confidence: 99%
“…28 Upon addition of DCl (4 equiv.) to 3a in Et2O, the homogeneous red solution turned into a yellow slurry immediately.…”
Section: Resultsmentioning
confidence: 99%
“…One of the key discoveries in this area was the isolation and characterization of bis-eneamido intermediates that form upon the treatment of the second-generation catalysts (second-generation refers to iron carbonyl ATH precatalysts with two imine donors, and a methylene linker between the imine and phosphorus moieties) with base ( Figure 1). 28 The bis-eneamido species were not active catalysts themselves, but gave a well-defined entry point into the activation process, which lead to catalytically active species. 30 Understanding the activation process, in turn, lead to the development of a more active third-generation of catalysts, where one of the imine donors has been reduced to an amino group.…”
Section: Introductionmentioning
confidence: 99%